Mediating and negotiating marital conflicts - Ellis, Desmond (Sage Publ., 1996)
Definition of concepts -- Theory. Theory of lawyer negotiations. Mediation -- Choice of mediation or the adversarial process -- Marital violence. Family violence approach. Compatibility with mediation -- Spousal violence : post-separation -- Power imbalances -- Issues and outcome -- Process, outcomes and satisfaction -- Compliance -- Economic consequences -- Effects on children